Participation and leadership in Latin America and the Caribbean - Valdés, Teresa (ECLAC SantiagoCL, 1999)
Deals with conceptual aspects pertaining to the socio-political participation of women and to the indicators. Presents the statistical information that has been collected on the presence of women in politics and society and on the progress that has been made in applying public gender equity policies.